THE IMPACT OF E-COMMERCE ON REGIONAL ECONOMIC DEVELOPMENT - Mirzakulov Bexzod Faxritdinovich, (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
E-commerce has emerged as a transformative force in the global economy, reshaping business models, consumer behavior, and regional economic dynamics. This study investigates the influence of e-commerce on regional economic development, emphasizing its role in fostering entrepreneurship, increasing market access, and stimulating local employment. Using a combination of qualitative case studies and quantitative regional economic indicators, the research highlights both the opportunities and challenges posed by e-commerce. The findings suggest that regions actively integrating digital trade platforms experience enhanced economic growth, innovation, and inclusivity, whereas underdeveloped areas risk lagging due to digital infrastructure gaps. This study underscores the importance of strategic policy measures to harness e-commerce for balanced regional development.